Semiconductor devices based on gallium arsenide with deep impurity centers - Khludkov, Stanislav S.; Tolbanov, Oleg P.; Vilisova, Marija Dmitrievna; Prudaev, Ilya A.; Tyazhev, Anton V. (TSU Press, 2024)
The monograph is generalization of the results of extensive research into structures and devices based on gallium arsenide with deep impurity centers carried out in Tomsk State University, the Siberian Institute for Physics and Technology and the Scientific Research Institute of Semiconductor Devices. Methods of doping GaAs with the impurities of the transition metals of Fe, Cr, Mn are presented and the GaAs properties are described. Much attention is given to the analysis of the electron processes in the complex structures based on the above material. The characteristics of a number of developed devices such as switching avalanche S-diodes, UV and IR photodetectors, ionizing radiation detectors and generators of rectangular and high-power delta pulses are presented. The prospects of using GaAs doped with transition metals in spintronics are considered.